Epidemiology of long‐stay patients in a university teaching hospital. Issue 5 (May 2017) - O'Sullivan, Kim; Martensson, Johan; Robbins, Raymond; Farley, KJ; Johnson, Doug; Jones, Daryl
Abstract : Background: Patients admitted to acute care hospitals may have multiple comorbidities, and a small proportion may stay for a protracted period. Aims: To assess the proportion of hospital patients who are long stay (≥14 days) and evaluate associations with baseline variables and subsequent inpatient morbidity and mortality. Methods: This is a retrospective observational study of patients aged ≥18 years staying in hospital for at least 24 h between 1 July 2013 and 30 June 2014. Results: There were 22 094 admissions in 15 623 patients. The median (interquartile range (IQR)) length of stay (LOS) was 4 (2–8) days, and 10% had a LOS >16 days. Long‐stay admissions comprised 13.1% of admissions but used 49.1% of bed days. Long‐stay admissions were more likely to be associated with intensive care unit admission (21.2 vs 6.0%), medical emergency team review (20.5 vs 4.3%) and a longer duration of mechanical ventilation ( P < 0.0001 all comparisons). Long‐stay patients were more likely to develop in‐hospital complications, were more likely to die in hospital (8.2 vs 3.1%) and were less likely to be discharged home ( P < 0.001 all comparisons). Multiple variable analysis revealed several associations with prolonged stay, including multiple admissions in the study period, the nature of the admitting unit, the Charlson comorbidity index at admission, admission from another hospital and any history of smoking. Conclusions: Patients staying at least 14 days comprised one seventh of hospital admissions but used half of bed days and suffered increased in‐hospital morbidity and mortality. Several pre‐admission associations with prolonged stay were identified.